Target selectivity of MAPK phosphorothioate antisense ODN on p42/p44, p38 MAPK, and JNK protein expression and its inhibitory effect on VSMC DNA synthesis - Huang Shao-ling; Ding Bo; Li Jiang; Yi Fu-xian; Liu Wen-lan; Yu Qing-sheng; Guo Zhao-gui (Acta Pharmacologica Sinica, 2016)
AIM: To analyze the target selective and sequence-specific inhibitory effect of mitogen-activated protein kinase (MAPK) phosphorothioate antisense oligodeoxynucleotides (ODN) on p42/p44, p38 MAPK, c-jun NH2-terminal protein kinases (JNK) protein expression, and DNA synthesis in vascular smooth muscle cell (VSMC). METHODS: Using a phosphorothioate-protected 17-mer antisense MAPK ODN directed against the initiation of translation sites of the p42/p44 MAPK isoforms by liposomal transfection to deplete cultured rat, rabbit, and fetal calf VSMC MAP kinases. The 17-mer sense and random sequence MAPK ODN were used as controls. After liposomal transfection, cells were exposed to 20% serum for 24 h, and then harvested in lysis buffer. P42/p44, p38 MAPK, and p46/p58 JNK protein expression were measured by Western blot. DNA synthesis was measured by [3H]thymidine incorporation. RESULTS: Treatment with MAPK antisense ODN (0.1-0.8 mumol.L-1) for 48 h reduced phosphored p42/p44 MAPK protein expression but without effect on p38 MAPK and JNK expression, and inhibited cultured rat, rabbit, and fetal calf VSMC [3H]thymidine incorporation stimulated by 20% serum in a concentration-dependent manner. CONCLUSION: The MAPK antisense ODN target-selectively and sequence-specifically reduces the p42/p44 MAPK protein expression and concentration-dependently inhibits proliferation of rat, rabbit and fetal calf VSMC.